Boosting teacher work engagement: the mediating role of psychological capital through emotion regulation - Ma, Yanfang (Frontiers in Psychology, 2023)
This study investigates the correlates of work engagement among English teachers by examining the mediating role of psychological capital between teacher emotion regulation and work engagement. A sample of 486 Chinese teachers took part in the research and filled out self-report measures of emotion regulation, psychological capital, and work engagement. Structural equation modeling was utilized to test the suggested mediation model. The outcomes showed that instructor emotion regulation was positively associated with both psychological capital and work engagement. Furthermore, psychological capital was reported to mediate the association between emotion regulation and work engagement. These findings highlight the importance of enhancing teacher emotion regulation and psychological capital as potential avenues for promoting work engagement among teachers.